GENDER DIFFERENCES IN SPEECH: A COMPARATIVE ANALYSIS OF ENGLISH AND UZBEK LANGUAGES - Muhammedova Mohichehra (Journal of Applied Science and Social Science, 2026)
This article explores gender-based differences in speech patterns in English and Uzbek languages from sociolinguistic and pragmalinguistic perspectives. The study aims to identify linguistic features characteristic of male and female speech and compare their usage across the two languages. The research employs qualitative and comparative methods, analyzing data from literary texts, media discourse, and everyday communication. The findings reveal that gender differences manifest in lexical choice, politeness strategies, emotional expressiveness, and discourse organization. While some similarities are universal, cultural norms significantly shape gendered communication in both languages. The study contributes to the broader understanding of language, gender, and culture interaction.